Measurement and analysis of needle penetration forces in industrial high-speed sewing machine - Carvalho, Helder (2009)
The industrial manufacturing of sewn products has always been one of the critical processes of the textile chain concerning quality assurance. Assuring the appropriate set-up and operation of all the machines, and thus the final seam quality, is a very complex task. Traditionally, this task is accomplished through empirical methods, with the machine setting and quality control relying on the skills of operators and technicians. This work presents an approach to a more knowledge-based and integrated process planning and control. A system was developed to measure and analyze the most important mechanical effects occurring during high-speed sewing. The paper will focus mainly on the measurement and evaluation of needle penetration and withdrawal force. After an overview of the system, the most important experimental results obtained in a series of experiments will be described.